Complementary Research Methods for Educational Leadership and Policy Studies (Springer International Publishing, 2018)
This edited volume brings together leading scholars from the fields of educational leadership and policy studies to discuss qualitative, quantitative, and mixed research methods in an accessible and pedagogically well-designed volume. Authors discuss ways in which various research methodologies and methods can productively be brought together to expand our current understanding of leadership issues and the contemporary policy context that surrounds them. Chapters provide both practical recommendations for using the methods discussed as well as suggestions for further reading. .